Environmental life cycle costing at the early stage for supporting cost optimization of precast concrete panel for energy renovation of existing buildings. (March 2021) - Zhang, Chunbo; Hu, Mingming; Laclau, Benjamin; Garnesson, Thomas; Yang, Xining; Li, Chen; Tukker, Arnold
Abstract: Around 35% of the buildings in Europe are over 50 years old and almost 75% of the building stock is energy-inefficient. A European project VEEP is developing an innovative prefabricated concrete element (PCE) system to improve the thermal performance of new buildings (PCE1) and old buildings (PCE2). This study focused on retrofitting of old buildings via over-cladding of the building envelope with PCE2. This study aims to from a building owner/consumer's perspective to explore the life cycle economic performance of the PCE2 system at an early stage and associated cost optimization strategies under the European context. This study tries to answer four questions: 1) whether the use of the PCE2 leads to an economic advantage over a specific life cycle of an existing building. 2) what is the biggest cost stressor in the life cycle of a PCE2? 3) the potential route for further cost optimization. and 4) how would the discount rate affect the life cycle costs, especially when Europe has entered a negative rate age? A typical apartment building in the Netherlands is selected as the case study for dynamic thermal simulation, in which the heating and cooling energy demands before and after refurbishment with PCE2 will be evaluated. By employing environmental life cycle costing (LCC), the life cycle costs over 40 years and associated strategy for cost optimization were investigated. This research not only unveils meaningful financial implications on resource-efficient building energy renovation in Europe but also provides insight on methodological dilemmas within the application of LCC. Highlights: Innovative technological systems for recycling construction and demolition waste (CDW) were introduced. A resource-efficient prefabricated concrete element (PCE2) system for refurbing existing building were presented. Economic implications on building renovation via prefabrication panel that included secondary raw materials are presented. The long-stand conceptual debates of environmental LCC were addressed.